PENGERTIAN DAN KEDUDUKAN EVALUASI DALAM PEMBELAJARAN - Ramadhan Syahrul Kamal Siregar (Jurnal Al Wahyu, 2023)
Evaluation is an essential process in education aimed at measuring students' learning outcomes. Evaluation plays a key role in helping teachers and students understand the extent to which learning objectives have been achieved. This article explains the concept of evaluation, the objectives of evaluation in the context of learning, and various evaluation methods used in education. A deep understanding of evaluation helps create a more effective and outcome-oriented learning environment.